Assessment of knowledge, attitude and practice of mothers/caregivers on infant and young child feeding in Assosa Woreda, Assosa Zone, Benshangul Gumuz Region, Western Ethiopia: a cross-sectional study - Dawit Getachew Assefa; Tigist Tekle Woldesenbet; Wondowsen Molla; Eden Dagnachew Zeleke; Timsel Girma Simie (BMC, 2021)
Abstract Background Through the health extension package, Ethiopia had practiced infant and young child feeding. However, infant and young child feeding (IYCF) practice has been poor. Hence, in this study, the knowledge, attitude, and practice of the mothers/caregivers on infant and young child feeding were assessed. Methods A cross-sectional study was carried out among 486 mothers/caregivers from Assosa Districts in the Assosa Zone of Benshangul Gumuz Region, Western Ethiopia. A semi-structured interviewer-administered questionnaire was used. To isolate independent predictors for good knowledge, good practice, and favorable attitude of the mothers/caregivers related to child feeding, multivariable logistic regression analyses were performed. Results Out of 486 study participants, 456 (93.8 %) of mothers had good knowledge, 432 (88.9 %) had a positive attitude, and 380 (78.2 %) mothers had good practice of IYCF practice recommendations. Furthermore, age of mothers, educational status of the mother, place of delivery, father's educational status, father's involvement & support, previous knowledge about IYCF, discussion with their husband about IYCF, and ANC follows up were significantly associated with mother's knowledge on IYCF recommendation. Conclusions Overall mothers had good knowledge and a positive attitude about IYCF practices. To support IYCF practices, behavior change communications intervention strategies should be introduced in mothers to bridge the gap between knowledge and practices.